The ghost in the city industrial complex: Le Corbusier and the fascist theory of Urbanisme. Issue 2 (2nd April 2016) - Brott, Simone
Abstract: In 1927 le Faisceau's newspaper Le Nouveau Siècle printed a feature "Le Plan Voisin" on Le Corbusier's 1922 redesign of Paris, including an extract Le Centre de Paris from his Urbanisme (1925). Le Corbusier's book was considered the "prodigious" model for the Fascist state that the league's leader Georges Valois called La Cité Française – after his mentor the French engineer and revolutionary philosopher Georges Sorel, who, originally on the radical left, would eventually be credited as the parent of twentieth-century fascist thought. Valois and Le Corbusier had inherited the longer genealogy of French thought from the turn of the century, namely the bitter opposition to the French revolution, and quarrel with the Enlightenment that was characteristic of many French intellectuals in the early twentieth-century. The final page of Urbanisme features a painting depicting Louis XIV ordering the construction of les Invalides (1670). "Homage to a great urbanist: This despot conceived great things and realized them." The image was produced at the dawning of the French enlightenment: its contents would become the precise object of the fin de siècle reactionary movements of the 1880s that gave birth to le syndicalisme. Le Corbusier thereby historicises his project for the new Paris.